Justification of the method of evaluation of the efficiency of air reconnaissance by unmanned aviation of ground (sea) objects - Brytov, O.; Bieliaiev, D.; Kukobko, S.; Chmil, Y.; Dzhus, V.; Herasymov, S.; Korobkov, Y.; Pomohaiev, I.; Roshchupkin, Y. (InterConf, 2021)
The paper considers the issues of assessing the effectiveness of air reconnaissance of ground (sea) objects by unmanned aerial vehicles. It is established that the main factors influencing the ability of air reconnaissance are the payload of the drone, the height and speed of its flight, the ability to transmit the information received. The main definitions that are the basis of the obtained results are given. Tasks for further research are set.
Keywords: unmanned aerial vehicle; efficiency; reliability; completeness